Overexpression of SHORT VEGETATIVE PHASE-LIKE (SVL) in Populus delays onset and reduces abundance of flowering in field-grown trees. (1st August 2021) - Goralogia, Greg S; Howe, Glenn T; Brunner, Amy M; Helliwell, Emily; Nagle, Michael F; Ma, Cathleen; Lu, Haiwei; Goddard, Amanda L; Magnuson, Anna C; Klocko, Amy L; Strauss, Steven H
Abstract: The spread of transgenes and exotic germplasm from planted crops into wild or feral species is a difficult problem for public and regulatory acceptance of genetically engineered plants, particularly for wind-pollinated trees such as poplar. We report that overexpression of a poplar homolog of the floral repressor SHORT VEGETATIVE PHASE-LIKE (SVL), a homolog of the Arabidopsis MADS-box repressor SHORT VEGETATIVE PHASE (SVP), delayed the onset of flowering several years in three genotypes of field-grown transgenic poplars. Higher expression of SVL correlated with a delay in flowering onset and lower floral abundance, and did not cause morphologically obvious or statistically significant effects on leaf characteristics, tree form, or stem volume. Overexpression effects on reproductive and vegetative phenology in spring was modest and genotype-specific. Our results suggest that use of SVL and related floral repressors can be useful tools to enable a high level of containment for vegetatively propagated short-rotation woody energy or pulp crops.